2005
DOI: 10.3354/dao064077
|View full text |Cite
|
Sign up to set email alerts
|

Parasite communities of Adriatic cage-reared fish

Abstract: From June 2001 to March 2002, 7 semi-offshore facilities in the Adriatic Sea rearing sea bass Dicentrarchus labrax, sea bream Sparus aurata, sharpsnout bream Diplodus puntazzo and red sea bream Pagellus bogaraveo aged 1+, were monitored for the presence of protozoan and metazoan parasites. Obtained data sets of abundance and prevalence were used to evaluate the structure and dynamic of infra-and component parasite communities. In all hosts, except the red sea bream, dominant parasites were monogenean specialis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 19 publications
4
56
1
Order By: Relevance
“…This is in accordance with the findings of Deviller et al (2004;2005), who found no difference in liver protein level between fish reared in RAS and RAS+HRAP after a one year period, reinforcing the hypothesis of a normal liver condition.…”
Section: Tissue Histology and Ultrastructuresupporting
confidence: 92%
See 1 more Smart Citation
“…This is in accordance with the findings of Deviller et al (2004;2005), who found no difference in liver protein level between fish reared in RAS and RAS+HRAP after a one year period, reinforcing the hypothesis of a normal liver condition.…”
Section: Tissue Histology and Ultrastructuresupporting
confidence: 92%
“…aequans is an almost unavoidable parasite in reared sea bass populations, causing mortalities in juvenile fish; its effects are often complicated in the summer months by secondary bacterial infections (Mladineo 2004). It can be isolated throughout the year, even though its occurrence is affected by environmental factors, especially temperature (Cecchini et al 1997;Cecchini et al 2001;Mladineo 2005). While both the RAS and RAS+HRAP showed the presence of this parasite, with a significant increase in numbers after one year of experimentation, no statistical evidence was found that one system represented better conditions for parasite propagation than the other.…”
Section: Parasitic Infectionmentioning
confidence: 97%
“…has been previously reported in S. aurata from France (Paperna and Baudin Laurencin 1979); several culture systems in Spain (AlvarezPellitero et al 1995); Adriatic Sea (Mladineo 2006) and different farming systems in Italy (Fioravanti et al 2006a, b). However, the taxonomic identity of the Trichodina species was not established.…”
Section: Discussionmentioning
confidence: 98%
“…They are likely to establish and proliferate in aquaculture because they may reproduce rapidly (Hutson et al, 2007). The presence of parasites throughout the year may be due to close and prolonged contact between fish in the same cage (Mladineo, 2006).…”
Section: Presence Of Parasites In Fish Farmsmentioning
confidence: 99%